KONSEP AKUNTANSI DALAM ISLAM - Syai’in; Afif, Abdullah (Irtifaq, 2019)
This article aims at discussing accounting concepts in Islam. The basicconcept of accounting has been explained in the al-Qur'an Surat al-Baqarahverse 282 which contains an obligation to record non-cash transactions. Thedevelopment of Islamic governments to the Middle East, Africa and Asia in theera of Umar Bin Khatab, second chaliph, has increased state revenues andexpenditures. Mu'amalah activities there are various types of shari'ahtransactions that have been implemented since the time of the Prophet until now.The shari'ah transactions include buying and selling transactions, servicetransactions, and transactions in the form of cooperation. Keywords: Muamalah, Accountancy, Registration